Boon or bane?: others' unemployment, well-being and job insecurity - Andrew E. Clark; Andreas Knabe; Steffen Rätzel (Center for Economic Studies and ifo Institute (CESifo), 2008)
The social norm of unemployment suggests that aggregate unemployment reduces the well-being of the employed, but has a far smaller effect on the unemployed. We use German panel data to reproduce this standard result, but then suggest that the appropriate distinction may not be between employment and unemployment, but rather between higher and lower levels of labour-market security. Those with good job prospects, both employed and unemployed, are strongly negatively affected by regional unemployment. However, the insecure employed and the poor-prospect unemployed are less negatively, or even positively, affected. We use our results to analyse labour-market inequality and unemployment hysteresis.
Keywords: D84; J60; Z13; 330; Unemployment; externalities : job insecurity; well-being; Arbeitslosigkeit; Regionaler Arbeitsmarkt; Arbeitsplatzsicherung; Sozialpsychologie; Lebenszufriedenheit; Deutschland